Component-based systems : estimating efforts using soft computing techniques - Seth, Kirti, 1966-; Seth, Ashish; Tripathi, Aprna (Boca Raton, FL : CRC Press, 2021)
"In order to survive in highly competitive market conditions and in a world of fast evolving technologies, businesses try hard to meet user needs along with keeping with the assurance of high-quality software. Soft computing techniques used to estimate the efforts that are invested in component-based software is a relatively new field of study. It covers the techniques needed to assess the efforts invested in building a software.This book is an important resource of information that will offer computer-based models used for estimating efforts of software. It will provide literature that gives an overview of component base software engineering, while addressing uncertainty involved in effort estimation and expert opinions. The book will also instruct the reader on how to develop mathematical models.This book will be an excellent source of information for students and researchers to understand and learn soft computing models, their applications used in software management, and will help software developers, managers, and those in industry to apply and use soft computing techniques to estimate efforts"--
1. Component Based Development. 2. Component Based Software Engineering. 3. Advantages of Component Based Software Engineering. 4. Problems and Pitfalls. 5. Efforts Estimation Techniques -- an Introduction and Review of Literature.6. Traditional effort Estimation Techniques. 7. Efforts Estimation in Object Oriented Systems. 8. Efforts Estimation in Component Based Systems. 9. Fuzzy Logic. 10. Estimating Component Selection Efforts -- A Fuzzy Logic Based Approach.11. Weight Assignment Technique for Component Selection Efforts. 12. Estimating Component Integration Efforts-A Neural Network Based Approach. 13. Neural Network Architecture and MATLAB NN Toolbox. 14. Conclusion.
OCLC-licensed vendor bibliographic record.
Keywords: Software engineering -- Management; Component software; Soft computing; TECHNOLOGY / Manufacturing; MATHEMATICS / General; COMPUTERS / Computer Science